Salivary Cortisol as a Stress Biomarker and Total Viable Count of Salivary Bacterial Microbiome among COVID-19 Patients - Hind H Enad; Abbas S .Al-Mizraqchi (College of Dentistry/ University of Baghdad, 2021)
Background: The COVID-19 virus outbreak had a massive effect on many parts of people's lives, as they were advised to quarantine and lockdown to prevent the virus from spreading, which had a big impact on people's mental health, anxiety, and stress. Many internal and external factors lead to stress. This negatively influences the body's homeostasis. As a result, stress may affect the body's capacity to use energy to defend against pathogens. Many recent investigations have found substantial links between human mental stress and the production of hormones, prohormones, and/or immunological chemicals. some of these researches have verified the link between stress and salivary cortisol levels. The aim of this study is to measure salivary cortisol as a stress biomarker as well as a total viable count of salivary bacterial microbiome among COVID-19 patients. Materials and methods: a sample of 84 adults patients was collected who were divided into two groups: the COVID-19 group consists of 42 patients and the COVID-19 free group which consists of 42 subjects. All subjects undergo a PCR test to confirm their health status. The collection of Un-stimulated saliva was done. Laboratory investigations were carried out to measure the total viable count of the salivary bacterial microbiome by culturing on Brain Heart Infusion Agar and to evaluate the salivary cortisol level using cortisol kit (Elecsys Cortisol II). Results: SPSS version 21 was used for statistical analysis. According to the statistical analysis, the salivary cortisol and total viable count of salivary bacterial microbiome values were substantially greater in the COVID-19 group than in the COVID-19 free group. Conclusion: A positive association was found between salivary cortisol and the total viable count of the salivary bacterial microbiome. So, when the concentration of salivary cortisol is elevated in the COVID-19 group, the level of the total viable count of the salivary bacterial microbiome is also elevated.